Correlation between Serum Caspase-1, IL-10, HOMA-IR, FAI, Dyslipidemia, and Oxidative Stress Status in Women with Polycystic Ovary Syndrome - Neelam Gusain; Ashish Anjankar; Ranjit Ambad (Journal of Pharmacy and Bioallied Sciences)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrinopathy characterized by hyperandrogenism, insulin resistance, and dyslipidemia. Inflammation and oxidative stress play critical roles in its pathogenesis. This observational cross-sectional study evaluated the relationship between serum Caspase-1, interleukin-10 (IL-10), homeostatic model assessment of insulin resistance (HOMA-IR), free androgen index (FAI), lipid profiles, and oxidative stress markers in women with PCOS. Materials and Methods: A total of 150 women diagnosed with PCOS participated in this study. Serum levels of Caspase-1, IL-10, HOMA-IR, FAI, lipid profiles (total cholesterol, low-density lipoprotein (LDL), high-density lipoprotein (HDL), triglycerides), malondialdehyde (MDA), and superoxide dismutase (SOD) were measured. Results: The results revealed significant elevations in Caspase-1, HOMA-IR, and lipid profiles, while IL-10 levels were lower compared to normal populations. Additionally, oxidative stress markers, including MDA, were significantly increased, while SOD levels showed a decline. Positive correlations were observed between Caspase-1, HOMA-IR, dyslipidemia, and oxidative stress markers. Conclusion: These findings suggest a crucial link between inflammation, insulin resistance, and oxidative stress in PCOS, contributing to its complex pathophysiology.